Organizational Factors Affecting Adoption of Electronic Medical Record (EMR) with Moderation of Openness to Experience - Lee, Jemimah Kezia; Antonio, Ferdi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Adopting electronic medical records (EMR) in type C hospitals is essential for improving patient quality and safety. However, resistance within the healthcare industry and reluctance to accept new technologies present significant barriers. This delay in EMR implementation affects the quality of patient care and public health. This research aims to analyze the organizational factors that influence the adoption of Electronic Medical Records (EMR). There are six independent variables related to the organization, namely Management Support, Adequate Training, Patient Safety Climate, Physician’s Involvement, Physician’s Autonomy, and Patient Relationship. These variables are related to two mediating variables from the Technological Acceptance Model (TAM) theory, Perceived Usefulness and Perceived Ease of Use, which directly influence EMR adoption, moderating by Openness to Experience. The method used in this research was a survey of medical health workers whose work was related to EMR. Cross-sectional data were taken from 205 respondents from two type C private hospitals in December 2023. The data analysis method used was Partial Least Squares-Structural Equation Modeling (PLS-SEM). The research findings show sufficient evidence to state that all independent variables have a significant and positive influence on Perceived Usefulness and Perceived Ease of Use (P-value <0.05, CI 95%). The strongest influence was found in Patient Relationship (β=0.501) and Patient Safety Climate (β=0.404). The results of this research can provide suggestions for improving patient conditions and illnesses, thereby enhancing the quality of care and benefiting the overall health of communities through the implementation of EMR.